A COMPARISON OF EFFICACY OF INTRANASAL FENTANYL AND INTRANASAL DEXMEDETOMIDINE AS PREMEDICATION IN PEDIATRIC PATIENTS - Rishikesh, Premgeeth; Joseph, Elizabeth; Joseph, Thomas (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objective of the study was to determine the effects of intranasal fentanyl compared to intranasal dexmedetomidine, when used for relieving pre-operative anxiety in children on the basis of onset and quality of anxiolysis, parental separation, hemodynamic stability, and cooperation to mask holding. Methods: A prospective observational study was conducted in Government Medical college Kottayam for a period of 12 months from December 2021 to December 2022, randomly assigned a total of 40 pediatric patients (the American Society of Anesthesiologists I and II) in the age group 3–6 years, undergoing elective surgeries requiring general anesthesia who received either intranasal fentanyl (group F) or intranasal dexmedetomidine (group D). Onset and quality of anxiolysis was compared using modified Yale pre-operative anxiety scale. Parental separation score, hemodynamic stability, and cooperation to mask holding were compared. Data collected were analyzed using SPSS version 25. Results: Children who received intranasal fentanyl as premedication had better quality and onset of anxiolysis as compared to dexmedetomidine group. In parent-child separation, intranasal fentanyl was found to be better than intranasal dexmedetomidine. Conclusion: We conclude that intranasal fentanyl is superior to intranasal dexmedetomidine in relieving pre-operative anxiety in pediatric population of age 3–6 years.